Stray animal complaint system using geolocation technique with rule-based Algorithm / Albin Lemuel Kushan … [et al.] - Kushan, Albin Lemuel; Mahadi, Mohamad Tajuddin; Zulhemay, Mohd Nabil; Sadikan, Siti Fairuz Nurr; Mishan, Mohd Taufik (Faculty of Computer and Mathematical Sciences, 2021)
In this current age, the world has become modernize with the advancement of technology, and with it, more countries are adapting to the ever-increasing technology trend. Subsequently, local council are also keen to veer towards this adaptation by introducing more technologically based type of services such as parking system using mobile application. Hence, this project is aimed to deal with issues in a more focus environment namely the stray animal issues in local community. Stray animal has become a nuisance to local community and in some cases, the result was fatal. Moreover, the increasing number of stray animals made the issue even harder to be kept under control. Therefore, this project intended to provide a better platform for local neighbourhood to file their complaint and the local council to address the filed complaint. Mobile application is chosen to be the main platform for the project, as it is much faster for the community to file a complaint as soon as a stray animal issue is noticed. In addition to that, geolocation technique is implemented to provide a better information in terms of the complainant’s location, and together with the utilization of a rule-based algorithms based on priority to provide the local council a better insight on the issue. Although more development is still needed for the project, initial testing shows that local council are able to provide a more efficient service to its local neighbourhoods by using the Stray Animal Complaint System mobile application.